Upper Clyde Shipbuilders Work-in, 1971 (1971)
1971 1960-2000 "Upper Clyde Shipbuilders Work-in, 1971" [T0420.jpg], 1971 The announcement of the withdrawal of government support for Upper Clyde Shipbuilders (UCS) was made in June 1971. The first redundancies were made on July 30 and the same day Jimmy Reid, the shop stewards' convenor, called for an occupation of the shipyards to prevent their closure. The work-in was supported by mass demonstrations and regional strikes, and only ended in October 1972 when the Government guaranteed work for all four shipyards on Clydeside with most of the original 8000 jobs retained. The UCS work-in stimulated a wave of workers' occupations throughout Britain, estimated at 190 between 1971-1975. This publication celebrating the UCS victory was produced in 1972 by printing workers involved in a work-in at Briant Colour Printing in London